THE COOPERATION OF PARENTS AND SPEECH THERAPIST IN THE TREATMENT OF SPEECH IMPEDIMENTS OF CHILDREN AT PRE-SCHOOL EDUCATION INSTITUTION - Rozenfelde, Mārīte; Čapkeviča, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The issue of the involvement of parents in the treatment of children with speech impediments in cooperation with speech therapists at pre-school education institutions is examined in the paper, as the correction of speech cannot be fully effective, if the family is not involved in the process. Parents' insufficient awareness on speech impediment and treatment, undervaluing the importance of speech impediments' early detection and timely actions, incorrect and sometimes harmful beliefs regarding child's speech, shows the necessity to cooperate at all the stages of treatment, provide parental education on the possibilities of children speech development. The author describes the research, carried out at a pre-school education institution, on the parents', whose children have speech impediments, perception of their role and the evaluation of their involvement in the speech impediments' correction, that proves that, estrangement occurs when children, being in specialized twenty-four hour care pre-school groups, do not receive the necessary interaction and overall development stimulating activities with their parents.